Financial Programming Is A Tool To Address Fiscal Policy Imbalances... Iraq Case Study - Hayder .H. Al-Bujabir; Qahtan Lafta Attia Al-Rubaie; Mohammed Shihab Ahmed (International Forum of Researchers and Lecturers, 2025)
Iraq needs to correct public finances to achieve stability and rebuild financial reserves, by adopting a program to measure and analyze the current situation and forecast macroeconomic policies to eliminate the imbalance between domestic demand and aggregate supply, which is usually manifested in the problems of the balance of payments, high inflation, and low output growth, and financial programming is an essential tool for managing policies to achieve stability and rebuild financial reserves.Analyze the current situation and forecast macroeconomic policies to address economic imbalances. However, there is a difficulty in applying the financial programming tool because of the lack of accurate information systems to estimate the rate of inflation, unemployment, economic growth, exchange rate, balance of payments and the general budget, in addition to irrational fiscal policy that depends on excessive expansion of government spending, with the sovereignty and control of the public sector over the macroeconomy, compared to the weak and weak role of the private sector. As a result of the policies pursued by successive governments and thus constitute weaknesses for the application of financial programming.